WHAT ARE CYTOKINES IN THE IMMUNE RESPONSE? (CIPEEX, 2025)
Therefore, the expressed increase in cytokines is induced by the presence of antigens, but they can renew their pressure and may be the same cytokines with positive or negative feedback. Cytokines then allow immune cells to communicate with each other, coordinating an effective response to pathogen attacks, acting both locally and at distant sites, affecting various cellular functions. They are produced by innate and assertive immunity in a brief and self-limited manner that only occurs in response to antigens. Receptors generally bind to their ligands with high affinity, resulting in small pieces of cytokines that are sufficient to occupy receptors and trigger biological effects. In this way, cells do not need to express their various receptors, which is why they are very important biologically. In this case, a process of macrophage inhibition is carried out to try to overcome the autoimmune response.
Keywords: Chemotaxis; Signs; Immune response; Treatment